2021
DOI: 10.1111/jop.13155
|View full text |Cite
|
Sign up to set email alerts
|

BRAF p.V600E status in epithelial areas of ameloblastoma with different histological aspects: Implications to the clinical practice

Abstract: Background: BRAF p.V600E is reported in up to 80% of ameloblastomas. Despite the high frequency, the presence of this mutation in different histopathological areas of the tumour has not been investigated. This information has an important role in the use of BRAF p.V600E assessment as an auxiliary tool in the differential diagnosis between unicystic ameloblastoma and other odontogenic cystic lesions, especially when only incisional biopsies are available. Therefore, the purpose of the present study was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…[4][5][6][7] From the demographic point of view, our unicystic ameloblastoma cases were predominantly observed in patients between the second and third decades of life, which is similar to other studies, 8,9 and in female individuals, contrary to what is observed in the literature. 2,10,11 This difference regarding gender can be explained by the reduced sample size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7] From the demographic point of view, our unicystic ameloblastoma cases were predominantly observed in patients between the second and third decades of life, which is similar to other studies, 8,9 and in female individuals, contrary to what is observed in the literature. 2,10,11 This difference regarding gender can be explained by the reduced sample size.…”
Section: Discussionmentioning
confidence: 99%
“…First described as a distinct entity by Robinson and Martinez in 1977, 1 unicystic ameloblastoma (UAM) is an encapsulated lesion which comprises 5 to 22% of all the diagnosed ameloblastoma cases. 2 It is often observed in patients between the second to third decades of life and presents a slight male predilection. Radiographically, it is mostly found at the posterior region of the mandible and usually presents as a unilocular image that may mimic some odontogenic cysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays a crucial role in regulating biological events such as apoptosis, differentiation and cell proliferation 6 . There is now increasingly robust evidence demonstrating that most ameloblastomas of all types harbour the activating v600e variant mutation of BRAF 7–10 . The role of BRAFv600e in ameloblastoma has gained clinical interest with the emergence of targeted therapy in the neoadjuvant setting 11–13 .…”
Section: Introductionmentioning
confidence: 99%
“…Solid/multicystic shows diverse subtypes. Although evidence on the molecular involvement of BRAF V600E mutant gene in the oncogenesis of mandibular AM and SMO in maxillary AM can be accepted now, surgical resection is the standard treatment because molecular-based therapy is still lagging [2][3][4]. Synchronous association of AM with other syndromes were observed in Gorlin syndrome, Gardner syndromes, epidermal nevus syndrome, Simpson-Golabi-Behmel Syndrome and Williams' syndrome [5,6].…”
mentioning
confidence: 99%